2015
DOI: 10.1126/sciadv.1500315
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of Lewis b antigen binding by the Helicobacter pylori adhesin BabA

Abstract: X-ray structure of BabA bound to Lewisb reveals molecular interactions used by H. pylori to colonize the gastric mucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
80
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 46 publications
(64 reference statements)
2
80
0
Order By: Relevance
“…S5 in the supplemental material). Adhesive proteins BabA and AlpAB are key factors in H. pylori adhesion that specifically bind to the cell surface proteins Lewis b and laminin, respectively (23,24). Results showed that PA significantly suppressed the adherence of H. pylori to GES-1 cells and inhibited alpA and alpB gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…S5 in the supplemental material). Adhesive proteins BabA and AlpAB are key factors in H. pylori adhesion that specifically bind to the cell surface proteins Lewis b and laminin, respectively (23,24). Results showed that PA significantly suppressed the adherence of H. pylori to GES-1 cells and inhibited alpA and alpB gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…There are 3 bab alleles (babA1, babA2, and babB) of H. pylori, but only the babA2 gene indicates Lewis-b binding function (6). The BabA adhesion of H. pylori is an external membrane protein that is attached to the fucosylated histoblood group antigens on the outer surface of gastric epithelial receptors (6,7). Duodenal users and adenocarcinoma H. pylori agglutinin (hpa) is a binding protein of H. pylori that is coded by the hpa gene and binds H. pylori to gastric mucosal cells.…”
Section: Introductionmentioning
confidence: 99%
“…Such recombination events can create ON/OFF switches, e.g., the babA1/babA2 variants, which result in gene silence (babA1) or expression (babA2) [16]. BabB is a non-Le b binding member of the BabA/B/C-family of proteins, with high similarities in the N-and C-terminal domains (and the corresponding gene segments), but extensive differences in the central region of the protein, and in particular in the Le b carbohydrate binding domain (CBD), which is only found in BabA protein [10,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…BabA belongs to a family that also includes the BabB and BabC proteins [13], that are very similar, but lack the Le b binding adhesin properties. The recent crystal structure of BabA revealed a distinct carbohydrate binding domain, which is missing in the closely related BabB protein [14,15]. The tight BabA-mediated binding and mucosal adherence result in chronic inflammation, with high levels of recruited inflammatory cells [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation